The Great Mass Emigration From Hungary to the United States, 1880-1914 - Bálint Lívia; Rusnik Kristina (2002)
n my thesis I elaborate on the topic of the Great Mass Emigration, that took place in Hungary between 1880-1914. The majority of the emigrants, forced by the circumstances, left their homeland, hoping a better life in the „land of opportunities ". 1 reveal the causes of the domestic migratory wave of the period. I examine the composition of the Hungarian Americans in different aspects, with the peculiarities of its temporal procession. I also demonstrate the initial distresses of everyday-life in the destination of emigration in consideration of their hazardous journey to America too. In the last part of my thesis I deal with the remigration of the Hungarians.
Keywords: Pedagógusképzés